THE IMPACT OF FINANCIAL REGULATIONS ON PROFITABILITY, GROWTH, AND RISK DISPERSION: EMPIRICAL EVIDENCE FROM AN EMERGING MARKET CONTEXT - Oyasor, Emmanuel Imuede (J-MACC : journal of management and accounting, 2026)
This study examines the effect of International Financial Reporting Standards (IFRS) adoption on firm performance among companies listed on the Johannesburg Stock Exchange (JSE) in South Africa. Using a balanced panel of 206 firms and 2,060 firm-year observations, the analysis compares pre-IFRS (2000–2004) and post-IFRS (2019–2023) periods based on changes in mean, median, and standard deviation of key accounting ratios. The results show that IFRS adoption is associated with notable improvements in average performance, with return on assets increasing by 45.480% and asset turnover by 0.660%. Growth opportunities also rise significantly by 72.890%, while firm size expands by 31.200%. However, return on equity declines marginally by 0.330% and cash flow by 5.410%. Importantly, variability increases substantially, with standard deviation rising by 202.630% for ROA and 441.390% for growth, indicating greater dispersion in firm outcomes. The findings suggest that IFRS enhances transparency and average performance but also reveals underlying heterogeneity. The study concludes that institutional quality and firm-specific factors are critical in shaping the IFRS–performance relationship.